Duro Olowu - seeing - Olowu, Duro 1965- (Museum of Contemporary Art Chicago, 2020)
"Published on the occasion of Olowu's largest curatorial project, Duro Olowu: Seeing elucidates the designer-cum-curator's creative process as he imagines relationships between artists and objects across time, media, and geography: Naomi Beckwith illuminates Olowu's curatorial process, driven by a voracious appetite for contemporary art and culture brought together in sharp juxtapositions. Valerie Steele situates Olowu's designs within the contemporary fashion world. Ekow Eshun focuses on Olowu's role within Britain's black and Afro-Caribbean creative community. Thelma Golden interviews Olowu about his work as designer, curator, and chronicler of culture and style across the worlds of museums and fashion. And Lynette Yiadom-Boakye creates new fiction for this volume." --Website
Impressum: This book is published on the occasion of the exhibition "Duro Olowu: Seeing Chicago", organized by Museum of Contemporary Art Chicago, February 29-May 10, 2020
Keywords: Olowu, Duro -- 1965-; Olowu, Duro / Exhibitions; Fashion designers / Nigeria / Exhibitions; Fashion designers; Nigeria; Exhibition catalogs; Ausstellungskatalog -- Museum of Contemporary Art -- 29.02.2020-10.05.2020 -- Chicago, Ill.; Bildband